(untitled) (The Journal of Psychology and Sociology, 2017)
The article gives the results of a sociological survey on the topic “Do you read of a book?” conducted by the Al-Farabi Kazakh National University. For today, the younger generation, are revealed the internal and external factors that are indicators of lowntrest to the book. The authors consider the enthusiasm of you thе technical means as one of the main problems leading to various adverse situations. So that young people the main tasks were reading books, need a lot of treatment and the appeals. Book reading on the one hand gives the opportunity to save energy and strength, on the other hand helps to facilitate addressing. It is written on the effectiveness of using the Internet to gain knowledge and information among student youth. Among young people entered the habit of constantly watch different programs on its own interests through the media. Our main task is to guide young people eto get information from the Internet that do not counteract the national mentality. In the article the author suffered several recommendations to improve the interest in reading books. The youth relation to reading begins to change in a positive side in recent years. The youth chooses to itself more convenient electronic versions of books. At Youth that fixed assets of information of steel for them the Internet and television. And it is valid, the truth. Practically each person has a mobile phone and Internet access where he can obtain information necessary for it. What are the benefits of reading books. And stress, as we know, the main problem of many working people. The rhythm of the written text and the wealth used in the writing of the author of the language tend to calm the mind and reduce tension from stress. Psychologists argues that a particularly effective fantastic works. As well as, the Development of thinking constantly practicing in this way, Your thinking will come to a new positive level. Reading books makes You more creative. What you need for creativity? Of course, good ideas! And book a huge number of them, maybe not noticeable at first glance. So You can use them for the realization in everyday life. Key words: Book, reading, Reading books, internet, youth, interest, mentality, mass- media.